Carrier-Based PWM Technique for Inverter-Fed Multiphase Induction Motor - Jyothi B; M.Venugopala Rao (Institute of Advanced Engineering and Science, 2016)
Multiphase (more than three phases) is very much popular due to their eminent features compared to conventional three-phase counter parts. In order to drive the multiphase machine, it requires same phase input w.r.t the no of phases at the output. This paper mainly focuses on five phase, because even after failure of one phase, the performance does not degraded much. Voltage source inverters (VSIs) are used to feed the induction motor. voltage source inverters (VSIs) switches are ON and OFF precisely to control the output. In order to implement harmonic waveform characteristic, carrier based PWM (pulse width modulation) is performed. By using with and without third harmonic injection machine torque is highly improved. Using MATLAB software, the simulation results are presented in the form of computer traces and high traded performance of the machine are discussed.